THE EFFECT OF TEMPERATURE DEPENDENT VISCOSITY ON THE STRUCTURE OF NEW PLUMES IN THE MANTLE: RESULTS OF A FINITE ELEMENT MODEL IN A SPHERICAL, AXISYMMETRIC SHELL - Kellogg L.H.; King S.D. (My University, 1997)
We have developed a finite element model of convection in a spherical, axisymmetric shell that we use to simulate upwelling thermal plumes in the mantle. The finite element method provides the flexibility to include realistic properties such as temperature-dependent viscosity, the focus of this paper. We used this model to investigate the effect of temperature-dependent viscosity on the structure of new plumes originating at the core-mantle boundary. Because the way in which mantle viscosity varies with temperature is not well constrained, we determined the plume structure using a variety of viscosity laws. We focus on 3 different viscosity laws: (1) constant viscosity; (2) weakly temperature-dependent viscosity, in which the viscosity increases by a factor of 10 between the hottest and the coldest material; and (3) strongly temperature-dependent viscosity, in which the viscosity varies by a factor of 1000. In a constant viscosity fluid, the plume exhibited a spout structure without a distinctive head. The plume head and tail consisted largely of material from the hot thermal boundary layer at the base of the spherical shell that represented the mantle. When the viscosity was strongly temperature-dependent, starting plumes developed a mushroom structure with a large, slow-moving head, followed by a narrow, faster moving tail. Material from the overlying shell was assimilated into the plume head during formation of the upwelling in models with strongly temperature-dependent viscosity, while the plume tail showed little entrainment. Constant viscosity models and models with weakly temperature-dependent viscosity showed almost no entrainment in the head or tail. The large plume head that formed in models with strongly temperature-dependent viscosity created and then shed ''blobs'' of material from the deep mantle that did not arrive at the surface near the plume but instead were deposited elsewhere in the upper mantle.
Keywords: MANTLE PLUMES; GEODYNAMICS; CONVECTION; HOT SPOTS